Knowledge, Attitude and Practice Regarding Immunization among Medical Students - Shrestha, Rubina; Chhettri, Pradip; Bhusal, Chet Kant; Ruchal, Rajendra; Shrestha, Saneep; Shrestha, Bipan (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Prevention of disease is the necessity of today’s life. Immunization is the most important component of preventive medicine. Knowledge and attitude of health professionals have significant role in increasing the acceptance of immunization. This study is aimed to determine the association between knowledge and attitude towards immunization and its practice among medical students and emphasis on the need of immunization education intervention among medical students. MATERIAL AND METHODS: Institutional based cross-sectional study among 397 medical students studying Bachelor in Medicine and Bachelor in Surgery (MBBS) was conducted in Universal College of Medical Sciences, Bhairahawa, Nepal. Purposively 1st to 4th year medical students were selected. RESULTS: Among 397 students, 59% had good knowledge regarding immunization, 63% had positive attitude and 47% had applied the knowledge and attitude in practice. Level of knowledge, attitude as well as practice regarding immunization was found statistically significant among medical students with their year of study. The analysis found that level of knowledge was more with 4th year students 89.47±7.92 and least with 1st year students 62.82±13.01. Third year and 4th year students had good attitude with mean score of 85.66±9.13 and 85.49 ± 9.51 respectively. Similarly, practice level was found more among 3rd and 4th year student, while least among 1st year students 39.89±21.16. There is statistically weekly positive correlation between knowledge, attitude and practice in overall among the medical students. CONCLUSION: The acceptance of immunization can be increased by increasing the level of knowledge and attitude regarding immunization thus providing a foundation to include a comprehensive immunization education to medical students.